POPULATION REDISTRIBUTION AND ECONOMIC GROWTH UNITED STATES, 1870-1950 - Lee, Everett S. (autor) (1957)
CONTENIDO: V. 1 METHODOLOGICAL CONSIDERATIONS AND REFERENCE TABLES. -- V. 2 ANALYSES OF ECONOMIC CHANGE. -- V. 3 DEMOGRAPHIC ANALYSES AND INTERRELATIONS